Network security: distributed intrusion detection system using mobile agent technology. (2016) - Boukhlouf, Djemaa; Kazar, Okba; Kahloul, Laid
Computer networks connected to the internet are always exposed to many kinds of cybercrimes. An internet user with malicious intent can access, modify, or delete sensitive information present on other computers or make some of the computer services unavailable to other users. An intrusion detection system (IDS) is the process of monitoring the events occurring in a computer system or network and analysing them for sign of intrusions. Centralised IDSs suffer from significant limitations when they are used in high speed networks, especially when they face distributed attacks. In this paper, we propose a distributed intrusion detection system based on mobile agents for network security. The proposed approach uses the platform aglets for the creation and the distribution of four types of mobile agents. A prototypical implementation is tested with different simulated attacks in an isolated network. The obtained results demonstrate the effectiveness of the proposed system.